Keynote Presentation: Improving Pavement Sustainability through Integrated Design, Construction, Asset Management, LCA, LCCA, and S-LCA - John Harvey (Engineering Proceedings, 2023)
Engineers, planners, asset managers, materials suppliers, contractors, and policymakers are focused on improving pavement infrastructure sustainability, and increasingly considering climate change resilience. This focus is often on materials; however, the decisions and practices in design, construction, and asset management are typically more important in achieving the desired environmental, cost, and social outcomes. This presentation discusses the tools of mechanistic–empirical design, asset management, performance-related tests and specifications, construction quality assurance, environmental and social life cycle assessment, and life cycle cost analysis, which can be used together to achieve the desired outcomes, and the data and models of which can be integrated in efficient web-based systems.